Enhancing Creativity of Generation Z Through Project-Based Learning - Juanda, Anda; Sudrajat, Anton (Ridwan Institute, 2026)
The development of creativity, especially among Generation Z students in high school, must be fostered through entrepreneurship education using an innovative and creative learning model: the Project Based Learning (PJBL) model. The purpose of this study is to test the effectiveness of the PJBL learning model in enhancing the creativity development of Generation Z students. The design of this study is a one-group pretest–posttest design. The sample in this study consisted of 125 State High School students representing four areas: Cirebon, Indramayu, Kuningan, and Majalengka Regencies, West Java Province, Indonesia. This research employed a creativity questionnaire adopted from Lawson. Data analysis included descriptive statistics, validity and reliability tests, normality tests, and hypothesis testing using the Paired Sample T-Test. Based on the research findings, the PJBL learning model effectively developed the creativity of Gen Z students. After the implementation of the PJBL learning model, the average student creativity score increased to 60.99, with the lowest score being 43 and the highest reaching 72, and a standard deviation of 6.237. Therefore, it can be concluded that the PJBL learning model increased students’ creativity by an average of 14.16. The aspects of creativity that improved among Gen Z students include fluency, flexibility, originality, and elaboration.